Anluwagi - Gojo Cruz, Genaro R.; Acuna, Pergylene; Chong, Grace Dacanay (Quezon City LG & M Corporation, 2013)
"Anluwagi tackles the issue of demolition and relocation from a child's perspective."
"Ages 7-13 y.o."
Text in English and Filipino.
Keywords: Children's stories, Filipino; Children's literature, Philippine; Carpentry -- Juvenile literature